In vitro comparison of the physical and mechanical properties of an ormocer with an ormocer‐based composite and a nanocomposite restorative material - Karien Jansen van Rensburg; Dorette Kritzinger; Samantha Arnold; Glynn D. Buchanan (Wiley, 2023)
Abstract Objectives To compare an ormocer with a first generation ormocer‐based composite and a nanocomposite in terms of surface roughness, surface hardness, and microleakage. Materials and Methods An ormocer (Admira Fusion), a first generation ormocer‐based composite (Admira) and a nanocomposite (Filtek Z350 XT) were prepared strictly in accordance with the manufacturer's instruction and recommendation to provide optimal material properties. Twelve disk samples of each material were evaluated to assess both surface roughness and surface hardness. For surface roughness, all samples were finished, polished, and Ra values measured with a profilometer. For surface hardness, samples were stored in an incubator, polished and a Vickers diamond indenter was used to record values. For microleakage, 36 standardized, Class V cavities were prepared and randomly divided into three groups. Restored teeth were thermally fatigued, immersed in 2% methylene blue solution for 48 h, sectioned, and scored for occlusal and gingival microleakage. Results Statistical significance was set at p < .05. The one‐way analysis of variance identified no significant difference in terms of surface roughness between the three material groups (p > .05). A significantly higher surface hardness was identified for the nanocomposite compared to both the ormocer (p < .001) and ormocer‐based composite (p < .001). Fisher's exact test identified no significant difference in terms of occlusal microleakage (p = .534) and gingival microleakage (p = .093) between the three material groups. Conclusions No significant differences in terms of surface roughness or microleakage were noted. The nanocomposite was significantly harder than the ormocer materials.